Hadrah Ishari Art: Ethnomusicological Study At Sirojul Huda Islamic Boarding School In Purwosari Pasuruan Regency - Larashati, Bunga Widiya; Yanuartuti, Setyo; Lodra, I Nyoman (Universitas Negeri Semarang, 2021)
This research aims to analyze the ethnomusicological study of hadrah ishari musical art. The type of research used is descriptive qualitative with an ethnomusicological approach. The data collection techniques are through observation, interviews, and documentation. Interviews were done with an informant who is competent in the art of hadrah ishari is Ichwan Mu'jizat. The data analysis steps are data reduction, presentation, and conclusions. The data validity was obtained through triangulation techniques of data sources and techniques. The results of the study show history, the form of presentation of this hadrah music consists of the introduction, the core, and the final presentation. The elements that make hadrah ishari music consist of tempos, rhythm, expressions, dynamics, and tone scales, while the elements that make the vocals of hadrah music are articulation, respiration, intonation, and tones. The movement of the head and hands also has a deep meaning about the symbol writing of Allah SWT and Muhammad SAW. The function of hadrah ishati itself has developed from the beginning for da'wah media, now it has begun to develop into entertainment, communication, commercial and creative media. Based on the results of the research, it is hoped that there are further researches and they can improve the results of the research, especially in the ethnomusicology study of the hadrah musical art. Keywords : History, Presentation Form, Elements of Music, Functions of Music